Using ecosystem services to identify inequitable outcomes in migratory species conservation. Issue 6 (10th September 2022) - Chester, Charles C.; Lien, Aaron M.; Sundberg, Juanita; Diffendorfer, Jay E.; Gonzalez‐Duarte, Columba; Mattsson, Brady J.; Medellín, Rodrigo A.; Semmens, Darius J.; Thogmartin, Wayne E.; Derbridge, Jonathan J.; López‐Hoffman, Laura
Abstract: Biodiversity conservation efforts have been criticized for generating inequitable socio‐economic outcomes. These equity challenges are largely analyzed as place‐based problems affecting local communities directly impacted by conservation programs. The conservation of migratory species extends this problem geographically since people in one place may benefit while those in another bear the costs of conservation. The spatial subsidies approach offers an effective tool for analyzing such relationships between places connected by migratory species. Designed to quantify ecosystem services provided and received in specific locations across a migratory species' range—and the disparities between them—the spatial subsidies approach highlights three axes of inequity: between indigenous and settler colonial societies, between urban and rural populations, and between the Global North and Global South. Recognizing these relationships is critical to achieving two mutually reinforcing policy goals: avoiding inequitable conservation outcomes in efforts to conserve migratory species, and ensuring effective long‐term conservation of migratory species. In demonstrating how the spatial subsidies approach enables the identification and quantification of inequities involving three migratory species (northern pintail ducks, monarch butterflies, and Mexican free‐tailed bats), we argue that a spatial subsidies approach could apply to migratory species conservation efforts worldwide under the context of "payments for ecosystem services."